Trends in the development of Fink’s taxonomy: a systematic literature review - Yaw, Patronella William; Mohd Matore, Mohd Effendi Ewan; Handayani, Trikinasih; Handayani, Lina (Journal of Education and Learning (EduLearn), 2025)
Fink’s taxonomy is a learning model of six interrelated elements that can be used for the development of learning goals and create significant learning. However, there has been limited discussion about the development trend of Fink’s taxonomy systematically. This study aims to identify trends in previous research that employed Fink’s taxonomy based on countries and current years, as well as the diversity of definitions of Fink’s taxonomy. This systematic review follows systematic reviews and meta-analyses (PRISMA) criteria and utilizes three main databases: Scopus, Web of Science, and ERIC. A total of 16 articles met the given criteria, and empirical results report that most studies on Fink’s taxonomy were conducted in the United States, with the highest number of articles published in 2020. Furthermore, the diversity of definitions of Fink’s taxonomy identified three themes which are producing significant learning, an approach that creates permanent changes in students, and focusing on the affective domain. The findings have significant implications through the introduction and understanding of Fink’s taxonomy. This trend can serve as a reference for the ministry of education and other stakeholders in the empowerment of Fink’s taxonomy in education. The study can be expanded by introducing new constructs for Fink’s taxonomy in the local context.